Peningkatan Perilaku Prososial pada Anak Usia 4-5 Tahun Melalui Kegiatan Outbond Fun Estafet di Tk PGRI Langkap Burneh Bangkalan - Dewi Mayangsari; Evi Dwi Novita Sari; Nofiana Munaila (PG-PAUD Trunojoyo, 2017)
Prosocial behavior is an important value in developing social relationships with the community environment starting with learning to adjust and cooperate in play activities. In Kindergarten PGRI Langkap, Burneh Bangkalan parents and teachers complain about the child's prosocial behavior is perceived as lacking. One strategy chosen to develop this aspect is to invite children to play outside the room, held a competition and usually called Outbond. Outbond activities in this research called Fun Outbond Esafet implemented in groups. The purpose of this study is the researchers wanted to know the effectiveness of activities Outbound Fun Relay in Kindergarten PGRI Langkap Burneh Bangkalan to improve prosocial behavior. The methods used Classroom Action Research. The results of this research, Outbound Fun Relay activities can improve the prosocial ability of children aged 4-5 years in Kindergarten PGRI Langkap, Burneh Bangkalan. The child's prosocial ability increased from 31% to 86.20% over two cycles.